Analysis of Strategies in Realizing a Sustainable Halal Fashion Industry - Wahyuni, Sri; Bin Sapa, Nasrullah; Muthiadin, Cut (IAIN Kendari, 2025)
The purpose of writing this article is to analyze strategies in realizing a sustainable halal fashion industry. The method used in writing this article is descriptive qualitative method, one of the indicators in the halal fashion criteria is environmentally friendly but on the other hand the presence of fast fashion is a fashion trend that changes and develops quickly and has a more affordable price but has a negative impact on the environment and social welfare.Therefore, there is sustainable fashion and ethical fashion as a solution to deal with the negative impact produced by fast fashion. The implementation of sustainable fashion and ethical fashion has a good impact on the environment. Therefore, with products and lifestyles that are in accordance with sustainable fashion and ethical fashion, the negative impact of fast fashion can be minimized.